Activities of daily living and its influencing factors for older people with type 2 diabetes mellitus in urban communities of Fuzhou, China - Jie, Jin-Hua; Li, Dan; Jia, Li-Na; Chen, Yifeng; Yang, Yan; Zheng, Bailing; Wu, Chuancheng; Liu, Baoying; Xu, Rongxian; Xiang, Jianjun; Zhuang, Hai-Lin (Frontiers in Public Health, 2022)
Background: Type 2 diabetes mellitus (T2DM) is an independent risk factor for functional limitations among the older population. The predicted increase in T2DM cases combined with the ongoing rapidly aging population may further burden the already overloaded healthcare system and aggravate the loss of economic self-sufficiency. This study aimed to investigate the activities of daily living (ADL) and its influencing factors on older people with T2DM, and to provide implications for the development and improvement of community nursing services in the context rapidly aging population in China. Methods: From March 2019 to June 2020, we conducted a cross-sectional questionnaire survey among older T2DM patients in Fuzhou, using a multi-stage cluster sampling approach. Functional status was measured by the Lawton ADL scale. Stata ‘nptrend’ test was used to examine the trend of ordinal variables on ADL. Non-conditional logistic regression was used to identify factors affecting ADL limitations. Results: A total of 2016 questionnaires were received, with a response rate of 96%. 12.4% of participants suffered from varying degrees of functional impairment. ADL limitations increased with age. More comorbidities were associated with a greater risk of developing functional limitations in ADLs. the following sub-groups were more likely to suffer from ADL impairment: those aged 70 and over years (OR=1.99, 95%CI 1.77-2.56), living in an aged care house or with spouse/children (OR=2.31, 95%CI 1.25-4.26), low monthly income (OR=1.49, 95%CI 1.28-1.64), without health insurance (OR=1.82, 95%CI 1.40-2.40), tight family expenses (OR=1.95, 95%CI 1.42-2.69), having stroke (OR=6.70, 95%CI 2.22-20.23) or malignant tumor (OR=4.45, 95%CI 1.27-15.53), irregular eating habit (OR=2.55, 95%CI 2.23-2.92), smoking (OR=1.40, 95%CI 1.22-1.60), sedentary lifestyle (OR=2.04, 95%CI 1.46-2.85), lack of physical exercise (OR=1.35, 95%CI 1.19-1.53), sleeping difficulty (OR=1.25, 95%CI 1.10-1.42), and lack of family support (OR=1.19, 95%CI 1.10-1.29). Conclusion: Older adults (≥70 years) with T2DM had a high prevalence of functional limitations across a range of daily living tasks, which not only affect individual life of quality but also present a huge burden on the family, health services system, and the whole society. Identified factors associated with ADL limitations may provide useful information for targeted nursing practice and health promotion.